A avaliação dos soft skills pelos executivos de ti na contratação do gerente de projetos - Fernandes, Nadia Pedrosa (2018)
The strategic importance of projects requires the hiring of project managers that meet the requirements agenda required by organizations. The literature suggests that there is a positive relationship between the project manager's competencies and project outcomes. Soft skills or interpersonal skills make up part of such skills. In this sense, more and more soft skills of the project manager are perceived as essential skills for organizations that aim to multiply their results. The difficulty in evaluating project managers and their soft skills arises. The objective of this research was to describe the process of evaluating soft skills in the hiring of the IT project manager, from the perspective of IT executives. The research brought a literature review to consolidate the main theoretical pillars: soft skills of the IT project manager and hiring the IT project manager and generated a theoretical framework that served as a foundation for later comparison between theory and research results. We opted for the qualitative approach whose method of research adopted involved interviews with IT executives from different business segments with experience in selecting candidates for the position of IT project manager. In addition to the interviews, a survey of job descriptions of IT project managers was conducted from an online job platform to compare information between academia and field research. Data analysis relied on the rigor of the ideal grounded theory method to explain social phenomena in which the theory was not exhausted. The study was conducted in Brazil. The results demonstrated a synergy between the soft skills contained in the job descriptions of LinkedIn IT project managers and the literature. Interviews with IT executives showed, in turn, that there are no scientific methods for evaluating soft skills of IT project managers, but rather empirical techniques of hiring practice. The academic contribution of this research was achieved by analyzing the data from which propositions about the subject emerged. As a final result, a list of practical requirements on the hiring process was generated for both IT executives and IT project managers who could assist them in future hiring.